Effect of somatostatin and its antagonist on morphine analgesia in mice. - Capasso Anna (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of somatostatin (SST) and its antagonist cyclo-(7-aminoheptanoyl-Phe-D-Trp-Lys-Thr [Bzl]) (SSA) on morphine-induced analgesia. METHODS: The pain assays were the hot plate and the tail flick test. RESULTS: SST or SSA per se administered intracerebrally at the doses of 0.1 and 1 mg/mouse did not change the pain threshold of mice both in the hot plate and in the tail flick test. However, at the higher dose (10 mg/mouse), SST and SSA decreased the pain threshold in the tail flick test only. SST and SSA administered at the dose of 0.1 mg/mouse did not change morphine-induced analgesia. By contrast, SST and SSA at the doses of 1 and 10 mg/mouse reduced morphine analgesia effects both in the hot plate as well as in the tail flick test. CONCLUSION: Our results indicate that SSA as well as SST may be useful in studying pain mechanisms.